Determinants of the effectiveness of education and training in Indonesian migrant workers - Somanedo, Ofri; Muhyadi, Muhyadi; Jabar, Cepi Safruddin Abdul (Edelweiss Applied Science and Technology, 2024)
This study explores the effectiveness of education and training programs for Indonesian migrant workers, who often seek employment abroad due to limited opportunities and low wages in their home country. The increasing numbers of migrant workers, combined with their significant economic contributions, highlight the need for effective training to enhance their self-reliance and reduce the likelihood of returning to overseas work. Employing a mixed-methods approach, the research identifies key determinants of program success, including financial literacy, self-management, motivation, and social support. The findings reveal that while macro-level policies are still insufficient, effective mapping and guidance at the micro level show promising results. Successful training programs positively impact the workers' independence, with those who acquire essential skills more likely to pursue entrepreneurship upon returning to Indonesia, rather than seeking further employment abroad. The study underscores the importance of incorporating financial and digital literacy, along with entrepreneurship training, into the curriculum to foster long-term economic independence for Indonesian migrant workers.